Ayurveda treatment approach to uterine fibroid based on Arbuda Chikitsa - Karunagoda, K.; Perera, P.K.; Senanayake, H. (Ayurveda Sameeksha, 2018)
The study is aimed to conduct pedagogical review for develop Ayurveda treatment methods....
Keywords: Arbuda Chikitsa; Ayurveda; Uterine fibroids